(untitled) (Research, Society and Development, 2022)
Objective: to report the experience of the members of the Extremoamor extension project, through health education actions for vulnerable pregnant women to avoid premature birth. Methodology: Experience report through educational actions in health using: conversation circles, dynamics and workshops, in places such as the CRAS of the city, High Risk and Hospital, with thematic divisions and among the members that make up the research body of the project, using creative and participatory strategies together with pregnant women. Result and discussion: The project was conceived and started actions in 2020 coordinated by a professor and nursing students linked to a private educational institution Faculty Gamaliel. The first works started were due to the month of Purple November, which is considered worldwide as the month alluding to prematurity. During 2020 and 2021, several educational lectures were developed in the primary, medium and high complexity care network for the target audience, covering topics related to prematurity, allowing for more information and developing a care look at the signs and symptoms that are indicative of prematurity. Take a premature birth as well as safety in the care of the baby in case the premature birth happens. Conclusion: Health education has been a very important tool for the prevention and reduction of the rates of health problems that are considered public health problems, bringing more information to the referring public. Therefore, the EXTREMOAMOR project has been achieving its objective by contributing to the prevention of premature birth.